HOME AUTOMATION BY VOICE COMMAND - Sales Rocha, Wesley; Anhesine, Marcelo Wilson (Revista Interface Tecnológica, 2020)
This work is a prototype developed for a home automation system, through voice command. The proposed project uses concepts of Internet of Things, which, through wireless connectivity, allows you to turn the lamp on or off and monitor the residence, using fire and gas leak sensors. The project consists of the ESP8266 micro controller, which was configured as a web server, which receives requests sent by the smartphone. When the user performs any action by voice command, the smartphone sends a request to the server, which in turn, processes the information and updates its web page, notifying the user through the smartphone screen if the request was successful. and if there is any risk of fire or gas leak in your home. The development of this prototype will allow greater accessibility and security, for the elderly or disabled, to be able to perform simple tasks and monitor their homes, through voice command, directed to the smartphone